Power Electronic Converters : PWM Strategies and Current Control Techniques - Monmasson, Eric. (London : Wiley, 2013)
A voltage converter changes the voltage of an electrical power source and is usually combined with other components to create a power supply. This title is devoted to the control of static converters, which deals with pulse-width modulation (PWM) techniques, and also discusses methods for current control. Various application cases are treated. The book is ideal for professionals in power engineering, power electronics, and electric drives industries, as well as practicing engineers, university professors, postdoctoral fellows, and graduate students.
4.3. Programmed harmonic elimination PWM4.4. Optimized PWM; 4.4.1. Introduction; 4.4.2. Minimization criteria; 4.4.2.1. Harmonic current; 4.4.2.2. Pulsation torque; 4.4.3. Applying optimization results; 4.4.3.1. Switching angle trajectories; 4.4.3.2. Control continuity over the entire operational range of the machine; 4.4.4. Principles of real-time generation; 4.5. Calculated multilevel PWM; 4.5.1. Introduction; 4.5.2. Calculated three-level PWM; 4.5.3. Calculated PWM with independent levels; 4.6. Conclusion; 4.7. Bibliography; Chapter 5: Delta-Sigma Modulation; 5.1. Introduction.
5.2. Principle of single-phase Delta-Sigma modulation.
Print version record.
Keywords: Electric current converters; Electric motors -- Electronic control; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- General; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- Integrated; Electric current converters; Electric motors -- Electronic control; Electronic books